Panic scrip of 1893, 1907 and 1914 : an illustrated catalog of emergency monetary issues - Shafer, Neil. (McFarland & Company, Inc., 2013)
"This extensively illustrated work catalogs all known U.S. emergency currency issues of the panics of 1893, 1907 and 1914. Nearly 900 photographs show most types of these privately produced substitutes for money. The book includes contextual historical information and authoritative appendices by Steve Whitfield on labor scrip and Loren Gatch on the background leading to these currency issues"--